DERITA PANITIA PENGADAAN TANAH BAGI PEMBANGUNAN UNTUK KEPENTINGANUMUM TERHADAP PENERIMAAN PEMBAYARAN GANTI RUGI PEMILIK TANAH - Syahril Syahril (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2023)
The land owner as the subject of receiving compensation for land that is freed in the context of land acquisition for development in the public interest has full and absolute responsibility for the land that is recognized as his own. The full and absolute responsibility of the land owner as the recipient of compensation cannot be charged or held accountable to other parties and this is in accordance with the applicable Civil Law which specifically regulates accountability in unlawful acts. Landowners as compensation recipients who violate the law and negligence can be subject to civil and criminal sanctions.Keywords: Suffering, Committee, Land Acquisition, Compensation.